The Forbidden Forest Myth as a Social and Ecological Asset in the Kajang Community - Dewi, Susi Fitria; Yulika, Febri; Wirdanengsih, Wirdanengsih; Maijar, Andri; Sulistijaningtijas, Erlina Pantja; Sakti, Reza Ginandha (SCAD Independent, 2025)
The construction of the forbidden forest myth within the Kajang indigenous community of South Sulawesi, Indonesia, transcends mere social practice, serving as a potential asset in natural resource management rooted in local wisdom—a crucial aspect that remains underexplored in existing literature. This study aims to address this research gap by elucidating the characteristics, factors, and implications of the forbidden forest myth’s construction as a valuable resource in ecologically-based natural resource management. Employing a qualitative descriptive case study approach, this study reveals three significant findings. Firstly, the forbidden forest myth constructed by the Kajang indigenous people has evolved into a social institution governing the management and utilization of natural resources. Secondly, the myth’s influence permeates virtually all aspects of Kajang’s indigenous life. Thirdly, the construction of this myth has fostered a proactive attitude towards natural resource management and utilization within the Kajang community. This study also recommends comparative analyses of values, norms, and local wisdom across various indigenous communities in the context of natural resource management practices.